The South African Broadcasting Corporation (SABC) and its 'crisis' of independence - Ngwenya, B; Ngwenya, B; Blessed Ngwenya (2015)
The subject of 'independence' of the South African Broadcasting Corporation (SABC) has emerged as a key issue in post-apartheid South African public discourse. While the importance of 'independence' has rarely been questioned, the term's meaning has been subject to fragmented understandings and vague interpretations. This thesis explores the origins of divergent conceptions of 'independence', examining how these conceptions are constructed by staff within the SABC. The central task of this thesis is to critically examine the contested concept of 'independence' a task it accomplishes by engaging with issues of power, knowledge and identity. To this end, the thesis reveals that the neo-liberal policies imposed by the Washington Consensus play a significant role in shaping conceptions of 'independence' through their power to dictate policy in countries in the Global South, including South Africa. This power, exercised through dominant Washington Consensus institutions, such as the World Bank and the International Monetary Fund (IMF), inform knowledge and identities at a local level through the adoption of neo-liberal macro-economic strategies, such as Growth Employment and Redistribution (GEAR). As a result, there is no local without the global. The engagement with issues of power, identity and knowledge and their relationships to how 'independence' is understood ensures that meanings of 'independence' are contested and that 'independence' is not an immovable edifice. 'Independence' is only a product of an evolving matrix, in which the staff of the SABC, who are divided into four different tiers, construct their own interpretations of 'independence', shaped by their understandings of both organisational and external factors, such as politics and advertisers, in relation to their work. Using data from interview respondents and an analysis of key public policy documents, this thesis presents two key processes that influence understandings of 'independence' and, therefore, link the SABC to the larger external socio-political environment. These two key factors, the commercialisation of the SABC and the African National Congress (ANC) power struggles have helped to shape the four conceptions of 'independence' advanced in this thesis: namely, the legalistic, anti-establishment, political and professional conceptions of 'independence'. At the core of this thesis are two questions: How do staff within the SABC construct and understand the meaning of 'independence' of the SABC, and what has influenced these conceptions in post-apartheid South Africa? Consistent with these research questions, the thesis is located within the interpretive tradition, since it seeks to understand the world of the SABC through the lens of its staff. To complement the interpretivist approach, the thesis situates the SABC and its understandings of 'independence' within the wider South African context, in which the meaning of 'independence' should also be understood as being inextricably intertwined with and a product of the shifting developmental state of the macro-economic environment. The critical political economy of the media is, therefore, used as an explanatory framework for understanding how the macro-worlds of politics and economic strategies intersect within the micro-world of the SABC to shape conceptions of 'independence'. The thesis concludes by arguing that it is not a strong and domineering state that seeks to control public service broadcasting; instead, it is a weak state that does so because of a need to curtail public discourse, which might present a threat to its own existence if left uncontrolled. As a result, it is difficult to separate the SABC from the state and, for that reason, the role of the public service broadcaster (PSB) is tied to the national narrative which itself is tied to the larger global matrices of power.